Latin America 2010: Social investment as a percentage of GDP (2014)
The main objective of this report is to make a comparative study of social investment for twenty Latin American countries. The social investment indicator is analyzed based on four aspects: (i) education, (ii) health services, (iii) housing, and (iv) general social assistance; all aspects are identified as percent ages of gross domestic product (GDP). Thus, social attention is estimated in function of the productive capacity of various nations. The methodology includes comparative analysis of determinants for poverty and destitution. The study presents analyses of graphics, statistical parameters, correlations, econometric models and cluster analysis procedures. The countries with greater levels of social investment are Argentina, Uruguay and Brazil; conversely, those with lower investment in this field would be: Guatemala, Honduras and Paraguay.